Pengaruh Harga dan Promosi Terhadap Loyalitas Transportasi Ojek Online Gojek di Makassar: Pengaruh Harga dan Promosi Terhadap Loyalitas Transportasi Ojek Online Gojek di Makassar - Bakhtiar, fauzia; Miftha Farild; Wahyudi (Study of Scientific and Behavioral Management, 2022)
The purpose of this study was to determine the effect of price and promotion on online motorcycle taxi customer loyalty in Makassar City. This research is associative research. This study looks for the relationship between price (X1), promotion (X2) and loyalty (Y). The population in this study were all online motorcycle taxi application users in Makassar. As for the sample of this study, the use of the Go-jek application in Makassar. Using primary data. Using a questionnaire in the form of a Likert scale to collect research data. The results of the study which were processed using SPSS, with a significance of 5% (0.05) showed that the price variable had a negative but not significant effect on loyalty. Promotion shows a significant positive effect on loyalty. While the price has a significant positive effect on promotion. Price and promotion have a significant simultaneous effect on loyalty. Likewise, the results of the path test show that there is an indirect effect of price on loyalty through promotion. Keywords: Price, Promotion, Loyalty, Ojek Online